Social food here and hereafter: Multiproxy analysis of gender-specific food consumption in conversion period inhumation cemetery at Kukruse, NE-Estonia. (September 2018) - Oras, Ester; Tõrv, Mari; Jonuks, Tõnno; Malve, Martin; Radini, Anita; Isaksson, Sven; Gledhill, Andy; Kekišev, Ott; Vahur, Signe; Leito, Ivo
Abstract: Current approaches in diet-related bioarchaeological research focus on establishing major developments in ancient societies, whilst small-scale and high-resolution studies of social constituents of past food consumption have gained far less attention. We conducted a multiproxy study of ancient diet in the 12th–13th century AD cemetery at Kukruse, NE-Estonia, in order to address the question of socially constrained food in the past. Two different food related archaeological sources – ceramic vessels and human bones – were investigated by applying organic residue (gas chromatography-mass spectrometry (GC-MS), bulk isotope ratio mass spectrometry (IRMS), gas chromatography-combustion-isotope ratio mass spectrometry (GC-C-IRMS)), and plant microfossil analysis for the first, and human bone stable isotope (IRMS) analysis for the latter. Results show that there was a gender and to some extent also age-specific food consumption by different community members at Kukruse: male (and some older female) diet was based on more aquatic and higher trophic level organisms, whilst younger females tend to feed on lower trophic level and potentially more herbivorous animals and their products. The paper emphasises the concept of past diet as a social phenomenon, the aspects of which can be best revealed with the help of multiproxy bioarchaeological analysis. Highlights: Pots and human bones from cemetery context were analysed for dietary reconstruction. Organic residue, plant microfossil and bone stable isotope analysis was conducted. Gender-specific diet followed in lifetime and funeral rituals was revealed.